O brinquedo na educação infantil: algumas reflexões do uso do brinquedo à luz da sociedade disciplinar foucaultiana - Souza, Letícia Rodrigues de [UNESP] (2014)
The importance of toys is thematic that has been showing to the understanding of children's learning and the studies of Michel Foucault are each time more if detaching to debate the problematic ones of the education. Under this assumption, one opted for the inquiry of qualitative nature that was carried out in a Municipal School of Early Childhood Education in the state of Sao Paulo, municipality of Rio Claro, involving a teacher who worked with children of four years and the twenty five students in this class. From the research question How to configure of the role of toy for the training of children in early childhood education concerning the Foucault's disciplinary society? We have tried to identify which positions have the teacher who works with early childhood education with regard to toys in accordance with important issues to Michel Foucault. To develop this study, we conducted field observations, daily records, photographic records, semi-structured interview and documentary analysis. The collected data were organized in four axes of analyses in order to achieve the research‘s specific objectives: a) We have a disciplinary school?; b) It's time to learn or is it time to play?; c) And the toys what are they for?; d) There are possibilities of transgression in school?. The analyses based on the theoretical contributions of Michel Foucault shows that early childhood education school, studied in this work, presents elements listed for disciplinary and format the body of children. In general, we noticed the use of toys to control student behavior and also spaces of resistance to this control within this school setting. With regard to toys, we note that there is a need to deepen on its potential to be used as pedagogical material within the early childhood education institutions